IMPROVING LEARNERS’ ENGLISH PROFICIENCY THROUGH LEARNING STRATEGY INSTRUCTION - SUSWATI HENDRIANI (Ta'dib, 2010)
English mastery  has  become more important in this era. English teachers, therefore,  are expected  to help students to get much success in their language learning by making them aware of the importance of their contribution in learning the language and, then, teaching them language learning strategies. The effectiveness of the instruction is really determined by both the teachers and the language learners. To be more effective, the instruction should be highly practical and useful for students  Key words: improving, foreign language learner, english proficiency, learning strategy, instruction